A new species of Crinibracon Quicke (Hymenoptera: Braconidae) parasitic on pupae of Hasora chromus (Cramer) (Lepidoptera: Hesperiidae) from India - Gupta, Ankita; Achterberg, Cornelis Van; Chitrala, Malathi (Zootaxa, 2016)
A new species, Crinibracon chromusae Gupta & van Achterberg sp. n., parasitic on pupae of Hasora chromus (Cramer) (Hesperiidae) on Millettia (= Pongamia) pinnata (L.) Panigrahi (Fabaceae), is described from India and compared with C. sinicus (Yang, Chen & Liu, 2008) from China, the only other species known with a similar general appearance. For the first time biological information for the genus Crinibracon Quicke, 1988, is given. Three species of hyperparasitoids, Philolema braconidis (Ferrière) (Hymenoptera: Eurytomidae), Nesolynx javanica Ferrière (Hymenoptera: Eulophidae), and an Eupelmus sp. (Hymenoptera: Eupelmidae) emerged along with C. chromusae sp. n. from pupae of H. chromus. The generic placement of this new species along with interesting parasitoid biology is discussed.